Electronic supplementary material from Freezer on, lights off! Environmental effects on activity rhythms of fish in the Arctic. - Kate L. Hawley; Carolyn M. Rosten; Thrond O. Haugen; Guttorm Christensen; Martyn C. Lucas (2017)
Supplementary methods and results